Fast road scenarios recognition of intelligent vehicles by image processing. (23rd November 2020) - Wu, Huawei; Li, Yicheng; Zhang, Jie; Kuang, Yong
Road scenarios recognition is a key point for intelligent vehicles (IVs) self-localisation. This paper proposes a fast road scenarios recognition method by image processing, which is based on a visual road model. First, a sequence of images is used to set up a visual road model. Second, we use the ORB method to encode both holistic and local features of a query image. Third, we extend the use of H-KNN to fuse ORB-encoded holistic and local features for road scenarios recognition. Real-world driving tests have been carried out in different routes scenarios. The total lengths of these routes are more than 5 km. The experiment results show that the proposed method achieved 80.2% image recognition rate, with about 18 ms in average for localisation from one image. The results demonstrate that the main method is promising in term of recognition accuracy and speed to develop low-cost recognition device for IVs.